Anti‐Yo mediated paraneoplastic cerebellar degeneration in the context of breast cancer: a case report and literature review. Issue 9 (14th April 2013) - Key, Richard Garrett; Root, James C.
Abstract Background Paraneoplastic syndromes are of interest to psycho‐oncologists because they may be misdiagnosed initially as primary psychiatric disorders and can have profound neuropsychiatric and psychosocial sequelae. Paraneoplastic cerebellar degeneration (PCD) is a paraneoplastic syndrome which destroys Purkinje cells of the cerebellum and causes trunk and limb ataxia, dysarthria, diplopia, and vertigo, which often precede the diagnosis of cancer. Anti‐Yo PCD is a devastating syndrome that significantly worsens prognosis in terms of functional ability and survival. Methods We present the case of a woman with progressive cerebellar deficits, which were misdiagnosed for several months before breast cancer and anti‐Yo antibodies were discovered. Results PCD may be misdiagnosed as a primary psychiatric disorder. Results of neuropsychological assessment in this case found subtle attentional dysfunction but relatively preserved cognitive functioning in other domains. Discussion The literature relating to PCD and psychiatric manifestations of cerebellar disease are reviewed. The limitations of our current understanding of non‐motor cerebellar function are highlighted, asserting the need for further study in this area. Copyright © 2013 John Wiley & Sons, Ltd.